2018
DOI: 10.1002/aocs.12038
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Partially Hydrogenated Rapeseed Oil During Repeated Frying Traditional and Fast French Fries

Abstract: The aim of this study was to compare thermal degradation of oil, especially the composition of the polymer in a polar and nonpolar fraction of oil, used for repeated frying of fast and traditional French fries. The French fries were fried using the partially hydrogenated rapeseed oil. Fast French fries were characterized by a half shorter frying time compared to traditional ones. The frying process was done at 170 C AE 5 C in 5-l electric fryers and carried out in 15-min cycles for 48 hours. The content of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The study of sunflower and high oleic sunflower oils also reported a significant increase of TPC: from 1.76% to 15.93% after 24 h of deep frying at 180 • C [49]. In addition, Kmiecik et al [50] reported that the final level of TPC in partially hydrogenated rapeseed oil used for frying the traditional and fast French fries was 6.3 and 5.3 time higher compared to fresh oil, respectively. The limit of TPC in oils differs depending on the country, e.g., Poland, Italy, Spain, France, and India have set a limit of 25%, Germany, of 24%, while Austria, Netherlands, Australia, China, and Switzerland have set it at 27% [35].…”
Section: Total Polar Compoundsmentioning
confidence: 93%
“…The study of sunflower and high oleic sunflower oils also reported a significant increase of TPC: from 1.76% to 15.93% after 24 h of deep frying at 180 • C [49]. In addition, Kmiecik et al [50] reported that the final level of TPC in partially hydrogenated rapeseed oil used for frying the traditional and fast French fries was 6.3 and 5.3 time higher compared to fresh oil, respectively. The limit of TPC in oils differs depending on the country, e.g., Poland, Italy, Spain, France, and India have set a limit of 25%, Germany, of 24%, while Austria, Netherlands, Australia, China, and Switzerland have set it at 27% [35].…”
Section: Total Polar Compoundsmentioning
confidence: 93%
“…PCA is one of the fundamental methods of chemometrics, and it was used for dimensionality reduction and for identification of the relationships between the variables and samples (Xu et al ., 2016). This method has been efficiently used in the study of polar compound composition of edible oils (Kmiecik et al ., 2017; Kmiecik et al ., 2018). Figure 1a demonstrates the PCA scatter plot that shows the classification among four types of vegetable oil samples on the basis of variations of polar compound composition induced by different treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with hydrolysed compounds, the resorption rate of OxTGs, TGDs and TGOs is high enough to induce toxic effects on animals (Li et al ., 2016). Moreover, TAG oligopolymers (TGPs, TGO + TGD) are important indicators related to the quality evaluation of edible oil and include a large complex group with the –C–C–, –C–O–C– and –C–O–O–C– linkages in their structure (Kmiecik et al ., 2018). The maximum TGP limit between 10% and 16% has been suggested in official legislations from different countries (Ahmad Tarmizi et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An oil sample was fractionated into the polar and non-polar fractions using silica gel, according to Kmiecik et al [47]. Briefly, the oil was dissolved in toluene and applied to a silica gel column.…”
Section: The Fractionation Into Polar and Nonpolar Fractionsmentioning
confidence: 99%
“…An oil sample was fractionated into the polar and non to Kmiecik et al [47]. Briefly, the oil was dissolved in tolue non-polar fraction was eluted with a mixture of hexane an fraction was eluted with pure diisopropyl ether.…”
Section: The Fractionation Into Polar and Nonpolar Fractionsmentioning
confidence: 99%